Peningkatan Keunggulan Kompetitif Perguruan Tinggi melalui Analisis Struktur Industri Porter - Rondonuwu, Robert Roy (FIkom Unisba, 2003)
The existence of competitive advantage for an organization is something that cannot be avoided. Globalization and hyper-competitive market condition makes the management try to consolidate and count their assests in order to definie the way and position that they want to achieve in the market. By using the business process reengineering, the organization can get new energy (revitalization) to make it one of the best in the competition. The objective of this paper is to motivate the organization by evaluating its internal condition in order to achieve the competitive advantage. The competitive advantage concept of Michael E. Porter is the central topic in all of the efforts to make the organization ambitions grow and expand in a dynamic market.